Factors impacting on retention, success and equitable participation in clinical academic careers: a scoping review and meta-thematic synthesis - Claire Vassie; Sue Smith; Kathleen Leedham-Green (BMJ Open, 2020)
Objectives To examine and synthesise current evidence on the factors that affect recruitment, retention, participation and progression within the clinical academic pathway, focusing on equitable participation across protected characteristics including gender, ethnicity and sexual orientation.Design Scoping review and meta-thematic synthesis.Data sources Web of Science, Google Scholar.Article selection We conducted a scoping review of English language articles on factors affecting recruitment, retention, progression and equitable participation in clinical academic careers published in North America, Australasia and Western Europe between January 2005 and April 2019. The most recent and relevant 39 articles were selected for meta-thematic synthesis using detailed inclusion/exclusion criteria.Data extraction The articles were purposively sampled to cover protected characteristics and career stages and coded for factors related to equitable participation. 17 articles were fully coded. No new themes arose after nine papers. Themes and higher level categories were derived through an iterative consensual process.Results 13 discrete themes of factors impacting on equitable participation were identified including societal attitudes and expectations; national and organisational policies, priorities and resourcing; academic and clinical workplace cultures; supportive, discriminatory and compensatory interpersonal behaviours and personal factors related to social capital, finances, competing priorities, confidence and ambition, and orientation to clinical, academic and leadership roles.Conclusions The broad and often interconnected nature of these factors suggests that interventions will need to address structural and cultural factors as well as individual needs. In addition to standard good practice on equality and diversity, we suggest that organisations provide equitable support towards early publication success and targeted mentoring; address financial and role insecurity; address the clinical workplace culture; mitigate clinical–academic–personal role conflicts and overload; ensure that promotional structures and processes encourage diverse applicants and promote family-friendly, coherent and transparent national career pathways.